2015
DOI: 10.1017/thg.2015.3
|View full text |Cite
|
Sign up to set email alerts
|

Low Birth Weight in MZ Twins Discordant for Birth Weight is Associated with Shorter Telomere Length and lower IQ, but not Anxiety/Depression in Later Life

Abstract: Shorter telomere length (TL) has found to be associated with lower birth weight and with lower cognitive ability and psychiatric disorders. However, the direction of causation of these associations and the extent to which they are genetically or environmentally mediated are unclear. Within-pair comparisons of monozygotic (MZ) and dizygotic (DZ) twins can throw light on these questions. We investigated correlations of within pair differences in telomere length, IQ, and anxiety/depression in an initial sample fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 85 publications
(115 reference statements)
1
17
1
Order By: Relevance
“…The present results align well with recent findings in twins discordant for birthweight : in monozygotic newborns with intra‐pair birthweight differences as little as between 0.1 and 0.3 kg, the heavier twin had longer telomeres, and the intra‐pair differences in birthweight correlated with the intra‐pair differences in telomere length; however, in dizygotic pairs with similarly discordant birthweights, no difference in telomere length was readily detectable, suggesting that genetic variation contributes more than minor environmental influences to the neonatal variation of telomere length. The present study design – with birthweight differences averaging as much as 1.0 kg or 2.4 Z‐scores between SGA, AGA and LGA subgroups – allowed to disclose that heavier singletons also have longer telomeres at birth than lighter singletons.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The present results align well with recent findings in twins discordant for birthweight : in monozygotic newborns with intra‐pair birthweight differences as little as between 0.1 and 0.3 kg, the heavier twin had longer telomeres, and the intra‐pair differences in birthweight correlated with the intra‐pair differences in telomere length; however, in dizygotic pairs with similarly discordant birthweights, no difference in telomere length was readily detectable, suggesting that genetic variation contributes more than minor environmental influences to the neonatal variation of telomere length. The present study design – with birthweight differences averaging as much as 1.0 kg or 2.4 Z‐scores between SGA, AGA and LGA subgroups – allowed to disclose that heavier singletons also have longer telomeres at birth than lighter singletons.…”
Section: Discussionsupporting
confidence: 91%
“…The present results align well with recent findings in twins discordant for birthweight (17): in monozygotic newborns with intra-pair birthweight differences as little as between 0.1 and 0.3 kg, the heavier twin had Figure 2 Correlations between telomere length at birth (expressed as normalized T/S ratio) and, respectively, lean mass (left panels) and fat mass (right panels) at ages 2 weeks (upper panels) and 12 months (lower panels), in the same 60 nonobese infants born large, appropriate or small for gestational age (LGA, AGA or SGA). P-values are from Pearson correlations, adjusted for sex and age.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers also have indicated that there were no difference between the RTL of preterm neonates and full-term newborns35. In addition, several studies observed that higher birth weight was associated with longer RTL3637, but which were inconsistent with our findings. Possible reason is that intra-uterine variables that affect newborn RTL are extremely complex, maternal psychosocial stress38, maternal estriol concentrations39, maternal Folate Concentrations40 and undetected factors might play an important role in affecting newborn RTL and disturbed the correlation between birth weight and RTL.…”
Section: Discussioncontrasting
confidence: 89%
“…As against the abovementioned studies, Strohmaier et al (2015) reported association of telomere length with birthweight in 16-yearold monozygotic twins but not seen in dizygotic twins. Raqib et al throughout life.…”
Section: Association Of Telomere Length With Anthropometric Variablmentioning
confidence: 86%
“…As against the abovementioned studies, Strohmaier et al () reported association of telomere length with birthweight in 16‐year‐old monozygotic twins but not seen in dizygotic twins. Raqib et al () reported significantly shorter lymphocyte TL in 5 years old preschool children ( n = 132) born with low birthweight compared with normal birthweight and suggested that this may be due to persistent immune activation because of high infection rate leading to higher T cell turnover.…”
Section: Discussionmentioning
confidence: 96%